U-Shaped and Surface Functionalized Polymer Optical Fiber Probe for Glucose Detection - Mikel Azkune; Leire Ruiz-Rubio; Gotzon Aldabaldetreku; Eneko Arrospide; Leyre Pérez-Álvarez; Iñaki Bikandi; Joseba Zubia; Jose Luis Vilas-Vilela (Sensors, 2017)
In this work we show an optical fiber evanescent wave absorption probe for glucose detection in different physiological media. High selectivity is achieved by functionalizing the surface of an only-core poly(methyl methacrylate) (PMMA) polymer optical fiber with phenilboronic groups, and enhanced sensitivity by using a U-shaped geometry. Employing a supercontinuum light source and a high-resolution spectrometer, absorption measurements are performed in the broadband visible light spectrum. Experimental results suggest the feasibility of such a fiber probe as a low-cost and selective glucose detector.